MISKONSEPSI MATERI ORGAN PEREDARAN DARAH DALAM PEMBELAJARAN IPA KELAS 5 DI SDIT ALAM NURUL ISLAM YOGYAKARTA - Farida, Jauharotul; Muhammad, Azamul Fadhly Noor (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is about finding and explaining the misunderstandings that fifth-grade students have about the human circulatory system while learning science at SDIT Alam Nurul Islam Yogyakarta. The research used a qualitative method with a descriptive design. The participants were fifth-grade students chosen using purposive sampling. Information was gathered through open-ended diagnostic tests, semi-structured interviews, and review of documents. The data was analyzed using an interactive model that included reducing data, displaying it, and drawing conclusions. To make sure the data was reliable, the study used multiple sources and methods for verification. The results show that students have some basic knowledge of the circulatory system, but they still have many misunderstandings. These mainly concern where and how the parts of the heart work, the difference between arteries and veins, and the paths of blood in the body and lungs. The overall path of the circulatory system was found to be the most misunderstood concept. Some reasons for these misunderstandings are that the teaching mostly uses lectures, there is not enough use of real or visual teaching tools, and students are not very involved in learning activities. The study suggests that teaching should focus on key scientific concepts, use real or visual tools, and involve students more in their learning to help reduce these misunderstandings.